Respiratory‐like movements during an apnea test - Shinichi Kida; Isao Nagata; Tetsuhiro Takei; Kazuhiro Yoshizawa; Taketo Suzuki; Hiroyuki Yamada; Yusuke Nakayama (Acute Medicine & Surgery)
Abstract Background Despite the possible occurrence of spontaneous movements during an apnea test, respiratory‐like movements are rare. Case Presentation A 51‐year‐old man was transferred to our hospital when a sudden disturbance of consciousness developed into cardiac arrest. After spontaneous circulation returned, we diagnosed bilateral cerebellar hemorrhage. He remained comatose with dilated pupils, absent brainstem reflexes, spontaneous breathing, and electrocerebral activity. After being considered brain dead, his family opted for organ donation. The first legal brain death examination on day 5 was aborted because of respiratory‐like movements mimicking repetitive abdominal respiration during the apnea test. However, an enhanced magnetic resonance image of the head indicated no blood flow and somatosensory evoked potential testing revealed no brain‐derived potentials. Conclusion Respiratory‐like movements can occur during the apnea test in patients considered brain dead. Further research is required to understand this phenomenon.